THE INFLUENCE OF TEACHER MANAGEMENT AND MOTIVATION ON TEACHER PERFORMANCE IN IMPROVING STUDENT QUALITY IN MADRASAH ALIYAH STATE 1 PRINGSEWU - Sudewi Sudewi; Muhammad Junaidi (Jurnal Ilmiah Ekonomi Manajemen: Jurnal Ilmiah Multi Science, 2019)
Madiahah Aliah Negeri 1 Peingsewu is one of the programs supporting the government, participating in the intellectual life of the nation, so that is also the reason for the purpose of Madrasah Aliah Negeri 1 Pringsewu. Management is a process of using organizational resources to achieve organizational goals through management functions. The school management that has been carried out so far has been maximized, that is, there are still management functions that have not been maximally implemented in school activities. Existing motivation within teachers will be heterogeneous in joining kapada organizations, this can be influenced by factors of education, personality and needs of each, with the provision of incentives will be able to narrow the differences in teacher goals as educators, so as to motivate teachers themselves so that eager to give high dedication to the Pringsewu 1 State Aliah Madrasah to support this goal all of course there are many indicators that influence it, while we highlighted in this study that is the influence of management and motivation that can affect teacher performance in improving the quality of students in the Pringsewu 1 State Islamic Senior High School. The purpose of this study is to find out (1) The effect of management on teacher performance in improving student quality (2) The influence of motivation on teacher performance in improving student quality (3) the effect of management and motivation on teacher performance in improving student quality. The results of the analysis and hypothesis testing provide conclusions that together management (X1) and motivation (X2) have a significant effect on teacher performance (Y) in improving the quality of student learning in Madrasah Aliah Negeri 1 Pringsewu. This is seen from the calculated Fcount value of 8.744 which is greater than the F value of 4.255. Partially, it is known that management (X1) and motivation (X2) significantly influence teacher performance (Y) in improving the quality of student learning at Pringsewu State Aliah Madrasa. This is shown from the tcount of the management variable (X1) = 3.696 and the tcount of the motivational variable (X2) = 4.073 which is greater than the t table value. Based on data and analysis qualitatively and quantitatively in this study, a conclusion can be drawn as follows: (1) There is a significant influence of management on the spirit of teacher performance in improving the quality of students in Pringsewu 1 State Islamic Senior High School. (2) There is a significant influence of motivation on teacher performance in improving the quality of student learning in Pringsewu's Aliah Negeri 1 Madrasah. (3) There is a significant influence of management and motivation together on the perf